Efektifitas Terapi Dzikir Untuk Menurunkan Tekanan Darah Pada Lansia - Mardiana; Irawati; Mas’ud, Alfian (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a resting or calm state. Treatment or management of hypertension takes a long time, lifelong and continuous. Efforts made in the management of hypertension are in the form of pharmacological efforts (drugs) and non-pharmacological efforts (lifestyle modification) in addition to non-pharmacological therapy, namely dhikr therapy. To see the effectiveness of dhikr therapy in lowering blood pressure in the elderly suffering from hypertension. Methods: This literature study method is carried out by searching for the results of scientific publications in the range of 2014-2024, using data based google scholar. In the data based google scholar using the keyword "dhikr therapy'' after being merged, 940 articles were found and the next search was combined using the keyword "blood pressure in the elderly" obtained a total of 720 articles. The search results of relevant articles after a full-text screening were carried out and sorted by relevance, with the last 10-year restriction finding 4 relevant articles. Results: The results of the article review showed that the four articles showed that dhikr therapy was effective in lowering blood pressure in the elderly Conclusion: This study proves that dhikr therapy can be used as a companion therapy or non-pharmacological therapy in lowering blood pressure. This therapy is safe and easy to do.